The primary way : philosophy of Yijing - Cheng, Zhongying, 1935-; Neville, Robert C. (Albany : SUNY Press, 2020)
In The Primary Way, the distinguished scholar of Chinese philosophy Chung-ying Cheng synthesizes his lifetime of work on the Yijing, also known as the I Ching or Book of Changes--Back cover.
Introducing the Yijing: six stages of development and six topics of the Yijing -- Yijing as creative inception of Chinese philosophy -- Interpreting a paradigm of change in Chinese philosophy -- Inquiring into the primary model: Yijing and Chinese ontological hermeneutics -- Philosophical significance of Guan: From Guan to onto-hermeneutical unity of methodology and ontology -- Yin-Yang way of onto-cosmic thinking and philosophy of the Yi -- On harmony as transformation: paradigms from the Yijing -- Zhouyi and the philosophy of Wei -- Li and Qi in the Yijing: a reconsideration of being and nonbeing in Chinese philosophy -- On the Yijing as a symbolic system of integrated communication -- On Zhu Xi's integration of Yili and Xianshu in the study of the Yijing -- On timeliness in the Analects and the Yijing: an inquiry into the philosophical relationship between Confucius and the Yijing.
Includes bibliographical references (pages 483-501) and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Yi jing; Yi jing; Philosophy, Chinese; Philosophie chinoise; Philosophy, Chinese; PHILOSOPHY / Metaphysics